Pollen germination and in vivo fertilization in response to high temperature during flowering in hybrid and inbred rice - Shi, Wanju; Li, Xiang; Schmidt, Ralf C.; Struik, Paul C.; Yin, Xinyou; Jagadish, Krishna S.V. (Wiley, 2018)
High‐temperature during flowering in rice causes spikelet sterility and is a major threat to rice productivity in tropical and subtropical regions, where hybrid rice development is increasingly contributing to sustain food security. However, the sensitivity of hybrids to increasing temperature and physiological responses in terms of dynamic fertilization processes is unknown. To address these questions, several promising hybrids and inbreds were exposed to control temperature and high day‐time temperature (HDT) in Experiment 1, and hybrids having contrasting heat tolerance were selected for Experiment 2 for further physiological investigation under HDT and high‐night‐time‐temperature treatments. The day‐time temperature played a dominant role in determining spikelet fertility compared with the night‐time temperature. HDT significantly induced spikelet sterility in tested hybrids, and hybrids had higher heat susceptibility than the high‐yielding inbred varieties. Poor pollen germination was strongly associated with sterility under high‐temperature. Our novel observations capturing the series of dynamic fertilization processes demonstrated that pollen tubes not reaching the viable embryo sac was the major cause for spikelet sterility under heat exposure. Our findings highlight the urgent need to improve heat tolerance in hybrids and incorporating early‐morning flowering as a promising trait for mitigating HDT stress impact at flowering.